Ectopic pregnancy in the uterus scar left after cesarean section: a clinical case - A. N. Rybalka; A. N. Sulima; D. А. Beglitse; O. A. Mitrofanova; O. S. Latyshev; I. О. Kolesnikova (Акушерство, гинекология и репродукция)
The article describes a rare clinical case of ectopic pregnancy in the uterine scar left after a cesarean section. The case demonstrates the complexity of diagnosing this abnormality and managing such patients. The proposed approach allowed us to diagnose pregnancy in the uterus scar in due time, avoid hysterectomy, and preserve the reproductive organ.